Total adiponectin, but not inflammatory markers C‐reactive protein, tumor necrosis factor‐α, interluekin‐6 and monocyte chemoattractant protein‐1, correlates with increasing glucose intolerance in pregnant Chinese–Americans (总脂联素，而不是炎症标志物包括C‐反应蛋白、肿瘤坏死因子‐α、白细胞介素‐6以及单核细胞趋化蛋白‐1与妊娠的华裔美国人的葡萄糖耐量受损加重有关). (26th February 2014) - Kim, So‐Young; Sy, Vanessa; Araki, Takako; Babushkin, Nicole; Huang, Diana; Tan, Doris; Liao, Emilia; Liu, George; Wan, Stephen; Poretsky, Leonid; Seto‐Young, Donna
Abstract Background Elevated insulin, C‐reactive protein (CRP), tumor necrosis factor (TNF)‐α, interleukin (IL)‐6, and monocyte chemoattractant protein (MCP)‐1 levels and decreased high molecular weight adiponectin (HMW‐APN) levels have been reported in Caucasians with gestational diabetes mellitus (GDM). No similar studies have been performed in Chinese women. Methods Serum samples were obtained 1 h after a 50‐g glucose challenge test (1HGCT) from Chinese–American women at 24–28 gestational weeks and total adiponectin (T‐APN), HMW‐APN, CRP, TNF‐α, IL‐6, and MCP‐1 concentrations were measured. Correlation coefficients for glucose (1HGCT), HbA1c, insulin, and body mass index (BMI) were calculated against T‐APN, HMW‐APN, CRP, TNF‐α, IL‐6, and MCP‐1. Significant P‐values were determined using Bonferroni adjustments. Results Women with GDM had higher insulin and 1HGCT and lower T‐APN. In addition, T‐APN was lower in non‐GDM subjects who had 1HGCT ≥135 mg/dL with no abnormal or one abnormal glucose value on the 3‐h oral glucose tolerance test. There were no significant differences in HMW‐APN and inflammatory marker levels between non‐GDM and GDM groups. There were negative correlations between T‐APN and 1HGCT, insulin, BMI, and HbA1c, as well as between HMW‐APN and 1HGCT, insulin, and BMI. No significant correlations were observed between 1HGCT, HbA1c, insulin, or BMI and CRP, TNF‐α, IL‐6, or MCP‐1. Conclusions T‐APN is reduced in Chinese women with GDM and those without GDM but with evidence of glucose intolerance. Unlike results reported for Caucasians, Chinese–American women with GDM do not exhibit elevated levels of CRP, TNF‐α, IL‐6, or MCP‐1, possibly because Chinese women are relatively leaner compared with Caucasians.